From guano to green hydrogen: food security and fertilizer disputes in international energy law - Hailes, Oliver (Journal of international economic law, 2023)
Abstract Russia’s invasion of Ukraine triggered energy and food crises, driven by demand for natural gas as fuel and fertilizer feedstock. By adopting a recent framework for analysing the diverse ways in which international law regulates energy transactions, I extend the category of end-use energy products to include food for human consumption, given the economic importance of dietary energy and the entangled agendas of energy and food security. To highlight the intermediate roles played by international law in securing resources for conversion into dietary energy, I show how rules allocating entitlements over fossil fuels were inherited from an earlier generation of international disputes over fertilizer resources, including the taxation of nitrate exports, alien entitlements to guano discoveries, and the well-known confiscation of a factory at Chorzów. Many of these disputes between States and commercial actors prefigured the reliance of the modern energy industry on investment arbitration and retain currency in case law. Yet, the fertilizer trade also informed the development of offshore resource entitlements, the local regulation of global externalities, and the belated recognition of the rights of peoples over natural resources. Despite this normative evolution, dispute settlement in the energy sector is still driven by States and commercial actors, although the underlying transactions may have profound implications for food security. By reframing food as energy and integrating fertilizer disputes into a long history of international energy law, the anticipated transition from fossil fuels towards green hydrogen as a dual-use fuel and fertilizer feedstock may generate familiar sites of distributive conflict over resources for the production of dietary energy, calling for closer attention to whether food security may be enhanced by the entitlements of collective subjects (food sovereignty), individuals (right to food), corporations (investment protection), and States (economic regulation).